Malaysian aviation technologist promotion to managerial role: an empirical overview - Liew, C. L.; Abu Talib, Abd. Rahim; Jacobs, Ronald Lynn (2016)
The Malaysian aviation industry has continued to march forward. With a turnover of RM23.7 billion in 2013, it is expected to grow higher especially after the Malaysian national aerospace blueprint was launched in 2015. The aviation related organizations currently have a workforce of approximately 13500. These organizations need to be managed by competent managers who have a strong background of technologist. Aviation technologist is one of the key components in the aviation maintenance industry as they are the future managers charged with the responsibility to ensure continuation of the organization's objectives and culture. The technologist role and manager's role are somehow different. The promotion of technologist to managerial roles is quite common but whether the technologist is able to take up managerial role effectively is yet to be fully understood. It is quite common that there was insufficient training for the technologist before being promoted to take up management roles. The purpose of this paper is to give an overview of the role of technologists and managers in professional services industries such as MRO and to understand that there is a need within the industry to re-look into the perspective of a proper training to prepare them to take up management roles effectively.